PENGARUH KESEHATAN KERJA, LINGKUNGAN KERJA DAN DISIPLIN TERHADAP PRODUKTIFITAS KARYAWAN DI PT CIPTA ADIL INDUSTRIES BATAM - Jeli; Wasiman (SCIENTIA JOURNAL, 2022)
Extraordinary skills and struggle because in the current era there are many competitors who are trying to get ahead and trying hard to be ahead of the market and they are trying to beat other competitors and do not care about entrepreneurs who want to grow because they want to be first and do not want anyone to compete with them. Therefore, it is necessary to establish yourself in action and make a mature and courageous decision to take risks, because in the world of business the road is not always smooth, but there will be various obstacles, both in terms of profit and loss. This analysis uses a quantitative method with SPSS 26 tools. The sample used is 130 respondents. Where there are no cases of heteroscedasticity and multicollinearity. While the overall f-test of the independent variables in the study together has a significant effect on the dependent variable